P114 Guidelines and selection criteria for lymphadenectomy in recurrent ovarian cancer patients. (1st November 2019) - Gallotta, V; Bruno, M; Conte, C; Giudice, MT; Davià, F; Lodoli, C; Federico, A; Santoro, A; Moro, F; Moruzzi, C; Fagotti, A; Scambia, G; et al.
Abstract : Introduction/Background: Several retrospective studies suggested that secondary cytoreductive surgery (SCS) could provide improved clinical outcomes in patients with recurrent ovarian cancer (ROC). The goals of this study were 1) to evaluate the prognostic role of clinico-pathological variables conditioning the post-salvage lymphadenectomy progression free survival (PSL-PFS) and 2) to assess which clinical and pathological parameters could drive to a personalized treatment. Methodology: Retrospective analysis of a single-institutional series of patients with lymph-nodal recurrence (LNR) managed with SCS at Our Institution, from November 2009 to September 2017. Results: Seventy two patients underwent SCS (48 laparotomic, 24 with minimally invasive approach). Median age was 58 years (range 37–78), median body mass index was 24.0 kg/m 2 (range: 17–35). The median platinum free interval (PFI) was 14 months (range: 6–175). Preoperative radiological work-up documented the presence of lymph node disease in aortic region (N=27, 37.5%), pelvic (N=21, 29.2%), and both aortic and pelvic (N=17, 23.6%), 5 (6.9%) at the level of hepato-celiac region, and 2 (2.8%) in hepato-celiac and aortic region. Ten patients (13.9%) were found to harbour other sites of disease associated with LNR. Systematic lymphadenectomy was carried out in 48 patients (66.7%), while bulky lymph nodes resection was performed in 24 patients. In all cases optimal residual was achieved. Adjuvant chemotherapy was administered to all patients. As of December 2018, median follow-up after SCS was 33 months (range: 11–111); relapse of disease was documented in 39 (54.0%) cases. Univariate analysis of variables conditioning PSL-PFS showed that the PFI before LNR >12 months, the negative Ca125 levels, number of metastatic lymph nodes <3, and documentation of isolate LNR played a statistically significant favorable role. Conclusion: Our data suggest that particular clinical and pathological features may improve selection criteria for SCS in ROC patients with LNR. Disclosure: Nothing to disclose.